TEACHING PEDAGOGY IN EDUCATIONAL INSTITUTIONS OF THE ORTHODOX CHURCH: VIEWS OF EDUCATORS AND RELIGIOUS FIGURES (1867-1884). - Tverdokhlib, Tetiana (Educological discourse, 2018)
The views of V. Belikov, A. Vasyliev, P. Lashkarov, P. Linytskyi, I. Malyshevskyi, A. Sheremetynskyi and other teachers and religious figures about teaching pedagogy in educational institutions of the Orthodox Church in 1867-1884 have been covered in the article basing on the analysis of primary sources and historical and pedagogical literature. It has been established that the theoretical groundwork on these issues was presented in the projects and publications of such ecclesiastical periodicals as Volynskie Eparxial'nye Vedomosti, Pravoslavnoe Obozrenie, Poltavskie eparxial'nye vedomosti, Trudy Kievskoj duxovnoj akademii, etc. The ideas of teachers and religious figures regarding the content, methodological support, organizational aspects, forms, staffing of teaching pedagogy in academies, seminaries and women's educational institutions of the Orthodox Church have been identified and considered. The comparative analysis of theoretical developments on pedagogical education in the Orthodox educational institutions of the early nineteenth century – the mid 60's of the nineteenth century and 1867-1884 has been carried out in the research. It was found on its basis that during the period under research the problems of teaching and methodological support and the organization of teaching pedagogy were rarely brought up by teachers and religious figures, but at the same time they joined to solving new issues. In 1867-1884 the works where the forms of organizing the process of teaching pedagogy, peculiarities of the activities of teachers of this discipline in the educational institutions of the ecclesiastical department were considered appeared for the first time.